10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Improper disposal of clinical and laboratory waste remains a major occupational and environmental health concern due to exposure to infectious, chemical, and pharmaceutical materials. This study assessed self-reported waste disposal practices and perceived environmental health risks among healthcare and academic personnel in Ekiti State, Nigeria. A cross-sectional descriptive study involved nurses, doctors, pharmacists, laboratory scientists, and students. A total of 450 questionnaires were distributed using stratified sampling, and 432 valid responses were analyzed (96.0% response rate). Data were collected using a structured questionnaire covering socio-demographics, knowledge, disposal practices, perceived risks, exposure incidents, and institutional support factors. Analysis included descriptive statistics, chi-square tests, and binary logistic regression at p < 0.05. The outcome variable was poor waste disposal practice based on composite scoring below the cut-off. Overall, 61.6% demonstrated good knowledge of waste disposal practices. Compliance was highest for sharps disposal (78.9%), while pharmaceutical waste disposal was lowest (48.6%). A total of 27.3% reported occupational exposure incidents, with needle-stick injuries most frequent (39.0%). Logistic regression showed that lack of training (odds ratio (OR) = 2.41, 95% confidence interval (CI): 1.52-3.83) and absence of color-coded bins (OR = 2.87, 95% CI: 1.74-4.72) were significantly associated with poor practice. These findings indicate that gaps in training and waste segregation infrastructure contribute to suboptimal practices and increased occupational risk. Strengthening training and improving waste management infrastructure may enhance safe disposal practices in healthcare and academic settings.